Study of the excess mortality associated with the SARS-CoV-2 pandemic in the Local Health Authorities and Districts of the Autonomous Region of Sardinia - quinquennium 2017-2021 - Pani, Sara Maria; Cadoni, Federica; Minerba, Luigi (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Based on the indications of the Italian National Recovery and Resilience Plan and the Ministerial Decree n°77/2022, detecting specific populations’ social-welfare needs is essential to reorganize the national and regional health service. The present analysis studies the impact of pandemic and pre-pandemic conditions in terms of mortality on Sardinian health service organizational subunits to indirectly investigate the need for specific social and health interventions. Design. Retrospective observational mortality study on the Sardinian resident population, surveyed by the Italian National Institute of Statistics (Istat) from 2017 to 2021. Methods. The database was built by crossing demographic data from the Istat divided into 21 five-year age groups (0-4 to 100+). Mortality and excess mortality were calculated with a focus on local health authorities and districts. The analysis were made considering three age groups (0-64, ≥ 65, 0-100+) and comparing the individual years 2020 and 2021 with the pre-pandemic triennium 2017-2019. To better understand the phenomenon of excess mortality, the old age index was calculated for the Local Health Authority and District for each year of the quinquennium considered. Results. Standardized mortality ratios increased in the biennium of the SARS-CoV-2 pandemic compared to the baseline 20172019. A global increaseof the Standardized mortality ratios in all districts (2021) was measured, including those with Standardized mortality ratios already increasing in 2020. Notably, the Standardized mortality ratios (2020 and 2021) were often increased by the 0-64 age group. The regional excess mortality (0-100+) confirmed an increase in mortality compared to the baseline, with a slight decrease from 2020 to 2021. Conclusions. Sardinia presents peculiar demographic and geographical characteristics. Monitoring mortality rates and excess mortality confirms to be crucial to constantly re-modulating health interventions and planning of the supply of services, including the equitable allocation of resources based on actual health needs. Sardinia should embrace the concept of “age-friendly community” and create communities designed to promote active aging and social participation.